1999
DOI: 10.1007/s004649901182
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic gastrostomy/jejunostomy (PEG/PEJ) for decompression in the upper gastrointestinal tract

Abstract: We believe that PEG/PEJ represents an effective, minimally invasive, and cost-effective method for gastrointestinal decompression in patients with advanced incurable cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 10 publications
0
16
1
2
Order By: Relevance
“…Percutaneous endoscopic gastrostomy (PEG) was initially developed to provide long‐term access for enteral nutrition, and has also been used for bowel decompression due to malignant and non‐malignant obstructions (decompressive PEG) . Although decompressive PEG is an effective alternative to nasogastric tube insertion, previous reports included relatively small numbers of patients and the details of post‐procedural outcomes and complications are lacking.…”
Section: Introductioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Percutaneous endoscopic gastrostomy (PEG) was initially developed to provide long‐term access for enteral nutrition, and has also been used for bowel decompression due to malignant and non‐malignant obstructions (decompressive PEG) . Although decompressive PEG is an effective alternative to nasogastric tube insertion, previous reports included relatively small numbers of patients and the details of post‐procedural outcomes and complications are lacking.…”
Section: Introductioncontrasting
confidence: 51%
“…Among previous reports regarding the pull method, wound infection and cellulitis with or without stomal leakage occurred in 4.7–21% of patients (Table ). Scheidbach et al . reported that in all patients, wound infections occurred irrespective of the use of prophylactic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only one patient underwent a gastrostomy to drain the bowel content, but in the study of Hull et al [9], 67% of the gastrostomies were performed in patients with bowel obstruction. There are also studies describing only gastrostomies for drainage [11,[13][14][15] showing satisfactory safety and significant improvement in the patients' quality of life.…”
Section: Discussionmentioning
confidence: 95%
“…Scheidenbach 1999].Auch zur Gastropexie bei intermittierendem Magenvolvulus ist die PEG verwendet worden [Altenwerth 1994]. Scheidenbach 1999].Auch zur Gastropexie bei intermittierendem Magenvolvulus ist die PEG verwendet worden [Altenwerth 1994].…”
Section: Klinikunclassified